Pengaruh Literasi Keuangan dan Kredit Usaha Rakyat Terhadap Peningkatan Pendapatan Usaha Mikro Kecil dan Menengah - Andi Priska Wulandari; Ismail Keri; Andi Patimbangi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
In this research, the author examines the influence of financial literacy and people's business credit on increasing the income of micro, small, and medium enterprises (a study of traders in Mare Market). The author collected data using descriptive research with a quantitative approach, gathering data through questionnaires and documentation such as books, journals, and internet sources related to this research. The data analysis tools included data quality tests, instrument tests, and hypothesis testing using SPSS version 26. Based on the research results and discussion, the author concludes that (1) the financial literacy variable (X1) has a partial and significant effect on increasing the income of micro, small, and medium enterprises (Y) among traders in Mare Market with tcount > ttable or 4.120 > 1.984 with a sig value of 0.000 < 0.05. Thus, Ha1 is accepted, (2) the people's business credit variable (X2) has a partial and significant effect on increasing the income of micro, small, and medium enterprises (Y) among traders in Mare Market with tcount > ttable or 5.310 > 1.984 with a sig value of 0.000 < 0.05. Thus, Ha2 is accepted, and (3) the financial literacy variable (X1) and people's business credit variable (X2) simultaneously influence the increase in income of micro, small, and medium enterprises (Y) among traders in Mare Market with Fcount > Ftable or 92.775 > 3.119 and a significance value of 0.000 < 0.05.